Concise Total Syntheses of Amorfrutin A and B. Issue 37 (4th October 2022) - Chen, Wenzhang; Xu, Tingxiao; Zhu, Gaofeng; Guo, Bing; Tang, Lei; Wang, Jianta
Abstract: The convenient and facile syntheses of amorfrutin A and amorfrutin B have been realized in five steps starting from commercially available 2, 4‐dimethoxybenzoic acid with an overall yield of 32 % and 22 %, respectively. The key steps involved Ru(II)‐catalyzed olefination and straightforward C‐alkylation. Abstract : The shortest synthetic routes for natural products amorfrutin A and B have been developed from the inexpensive material 2, 4‐dimethoxybenzoic acid. This work provides an opportunity for access to the synthesis of analogs.